Benchmark Load Testing Multi Skenario Aplikasi SiPADUKA V2 pada Shared Hosting - Muhammad Agus Triawan; Husnawati; Ahmad Bahri Joni M; Ridho Rahmatullah; Bagus Ananta Hidayatullah; Mohd. Ginar Risky (Universitas Muhammadiyah Muara Bungo, 2026)
Public service Web applications require adequate performance to ensure stable access when handling user load. SiPADUKA V2, an Information System for Reporting Child Abuse, was developed using native PHP MVC, MySQL PDO, Bootstrap, and JavaScript, and deployed on cPanel-based shared hosting. This study aims to establish the baseline performance of SiPADUKA V2 through an empirical benchmark using the load testing (LT) method. The testing was conducted using Apache JMeter 5.6.3 across four scenarios, namely LT1, LT2, LT3, and LT4, with 5, 10, 25, and 50 virtual users, respectively. The test plan consisted of three Thread Groups representing public pages, user pages after login, and admin pages after login. The analyzed metrics included Total Requests/Samples, Average Response Time, Throughput, and Error Rate. The results show that the total number of requests increased from 857 requests in LT1 to 5,180 requests in LT4, while throughput increased from 4.80 req/s to 27.68 req/s. The average response time was recorded at 383.94 ms in LT1, 342.40 ms in LT2, 289.72 ms in LT3, and increased to 589.72 ms in LT4. The error rate was 0.12% in LT1, 0% in LT2 and LT3, and increased to 4.05% in LT4. These findings indicate that SiPADUKA V2 remained relatively stable up to 25 virtual users but began to experience performance pressure at 50 virtual users.